(untitled) (Khairulummah, 2023)
Islam is a religion that has provided all the principles and rules of living to its followers. Islam gave utmost importance to ethics because this is the soul of the religion that is why the Sufis repeatedly taught it. Ethical values ​​are an important element of society and they are like the backbone of society, whether it belongs to any society, nation or religion. Coexistence in the society depends on the observance of moral values. Those nations reached the pinnacle of development, which practiced moral values, and those nations stood on the verge of destruction and destruction, which abandoned moral values. The requirement is to bring the human beings away from all these vices and bring them to the virtues so that the man can regain his lost position. Allah Almighty sent prophets for the reformation of man. These prophets worked for the moral and spiritual training of their respective nations in their respective eras. The way of living in the society, keeping in mind the principles of ethics, what is the way of living of a human being in the society, it is taught by innumerable Sufis in their own ways. If the man of the modern age keeps in mind the teachings of all these Sufis and follows their teachings, he can find the solution to the contemporary moral problems and attain the status of Ashraf-ul-Khalq in the true sense.